Talleres socioprofesionales "Las Naves" : Un proyecto de educación integral para la inserción sociolaboral de jóvenes - Sánchez, Luis Fernando; Moreno, Santiago (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2001)
The authors of this article show an experience of social-educational intervention, the so-called Social-Professional Workshops "Las naves", which are the result of many years of effort, joy and work in team. These workshops were born in Alcalá de Henares (Madrid) as a response to the necessities of training of a group of young people, who did not find within the official system what they required.